2018
DOI: 10.1111/iju.13796
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of elastic fusion biopsy in daily practice: Results of a multicenter study of 2115 patients

Abstract: Objectives To assess the accuracy of Koelis fusion biopsy for the detection of prostate cancer and clinically significant prostate cancer in the everyday practice. Methods We retrospectively enrolled 2115 patients from 15 institutions in four European countries undergoing transrectal Koelis fusion biopsy from 2010 to 2017. A variable number of target (usually 2–4) and random cores (usually 10–14) were carried out, depending on the clinical case and institution habits. The overall and clinically significant pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 26 publications
1
14
1
Order By: Relevance
“…A recent large multicentre study examining detection of clinically significant PCa in 640 men undergoing imagefusion transperineal biopsy found that the addition of nontargeted systematic transperineal biopsies only detected an additional 0.8-1.1% of clinically significant PCa when combined with image-fusion TBx [31]. Comparing transperineal template saturation biopsy to transperineal TBx (BiopSee â system), Radtke et al [32] showed that 7% of GS [32,34,35]. Based on these findings, while transperineal TBx and other fusionbased TBx platforms appear to improve the sensitivity of SBx for the detection of higher-risk cancers, there would still be an unacceptable level of missed clinically significant disease using TBx alone; therefore, we continue to advocate the combination of targeted with systematic biopsies at this time.…”
Section: Discussionmentioning
confidence: 99%
“…A recent large multicentre study examining detection of clinically significant PCa in 640 men undergoing imagefusion transperineal biopsy found that the addition of nontargeted systematic transperineal biopsies only detected an additional 0.8-1.1% of clinically significant PCa when combined with image-fusion TBx [31]. Comparing transperineal template saturation biopsy to transperineal TBx (BiopSee â system), Radtke et al [32] showed that 7% of GS [32,34,35]. Based on these findings, while transperineal TBx and other fusionbased TBx platforms appear to improve the sensitivity of SBx for the detection of higher-risk cancers, there would still be an unacceptable level of missed clinically significant disease using TBx alone; therefore, we continue to advocate the combination of targeted with systematic biopsies at this time.…”
Section: Discussionmentioning
confidence: 99%
“…Median duration of the surgical procedure was of 82 [44-170] min, including a median time of 16 [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] and 2 [2][3][4][5][6] min for MRI-ultrasound fusion and targeting, and microwave application, respectively (Fig 3). Microwave ablation was set at 15W for 3 min, 15W for 2 min, and 10W for 2 min, in 3 (30%), 5 (50%), and 2 (20%) patients, respectively.…”
Section: Intra and Post-operative Outcomesmentioning
confidence: 99%
“…Interest in FT has recently been renewed owing to improved biopsy and imaging techniques, allowing a more comprehensive management of the index tumor. The ability of magnetic resonance imaging (MRI) to detect significant cancer foci [4][5][6][7][8][9], together with the reliability of organ-based tracking (OBT) MRI-ultrasound fusion [10][11][12], now allows clinicians to detect and target the index tumor precisely: Performing an elastic fusion between MRI and ultrasound images can create a precise three-dimensional mapping of the prostate, accurately showing the index tumor. OBT enables physicians to guide and to distribute, in a realtime fashion, the biopsy cores in three-dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…When using the cited guidance systems, in order to map MRI targets to the US data, urologists have first to segment the prostate on the first acquired US volume (named panorama or reference volume). Moreover, during the intraoperative phase, the guidance software provided by the platform, also estimates the 3D/3D rigid transform between the reference volume and volumes acquired whole along the biopsy procedure using a widely evaluated image-based registration [7,14]. This transform will be considered as the ground truth T GT for this evaluation.…”
Section: Ground Truthmentioning
confidence: 99%